PRODUKTIVITAS PENGARANG ARTIKEL BIDANG ILMU PERPUSTAKAAN DAN INFORMASI DI INDONESIA TAHUN 1978-2007: ANALISIS BIBLIOMETRIKA MENGGUNAKAN HUKUM LOTKA - Nelisa, Malta (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2009)
The purpose of this research is to identify the productivity pattern of article in Indonesia 1978-2007, and it is to test and analyze the productivity distribution of article author in the field of Library and Information. This research uses quantitative approach through bibliometric analysis based on Lotka’s law. The data of this research is taken from the Index of Indonesian Learned Periodicals and database of PDII LIPI from 1978-2007. It is found that there are 826 authors and 1245 articles of Library and Information Science. The result of this research shows that the rate of the authors contribution to one article is 66.02 percent. Goodness-of-fit test using Kolmogorov-Smirnov test indicates that critical value in 0.05 is 0.0473 and maximum deviation value is 0.0775. It means that the maximum deviation is bigger than critical value, so the null hypothesis is rejected and difference between the Lotka’s law theoretic distribution and the distribution of article authors in the field of Library and Information Science.